Key Considerations for the Use of Seaweed to Reduce Enteric Methane Emissions From Cattle - Vijn, Sandra; Compart, Devan Paulus; Dutta, Nikki; Foukis, Athanasios; Hess, Matthias; Hristov, Alexander N.; Kalscheur, Kenneth F.; Kebreab, Ermias; Nuzhdin, Sergey V.; Price, Nichole N.; Sun, Yan; Tricarico, Juan M.; et al. (Frontiers in Veterinary Science, 2020)
Enteric methane emissions from livestock are the single largest source of direct greenhouse gas emissions (GHGs) in beef and dairy value chains and a substantial contributor to anthropogenic methane emissions globally. In late 2019, the World Wildlife Fund (WWF), with the Advanced Research Projects Agency-Energy (ARPA-E) and the Foundation for Food and Agriculture Research (FFAR) convened approximately 50 stakeholders representing research and production of seaweed, animal feeds, dairy cattle and beef and dairy food companies to discuss challenges and opportunities associated with the use of seaweed-based ingredients to reduce enteric methane emissions. This Perspective article describes the considerations identified by the workshop participants and suggests next steps for the further development and evaluation of seaweed-based feed ingredients as enteric methane mitigants. Although numerous compounds derived from sources other than seaweed have been identified as having enteric methane mitigation potential, these mitigants are outside the scope of this article.